Solitude profiles and psychological adjustment in Chinese late adolescence: a person-centered research - Zhou, Tong; Liao, Longyue; Nguyen, Thuy-Vy T.; Li, Dan; Liu, Junsheng (Frontiers in Psychiatry, 2023)
Objectives: From the perspective of person-centered research, the present study aims to identify the potential profiles of solitude among late adolescents based on their solitary behavior, motivation, attitude, and time alone. In addition, to echo the paradox of solitude, we further explored the links between solitude profiles and adjustment outcomes.Methods: Participants were 355 late adolescents (56.34% female, M age = 19.71 years old) at three universities in Shanghai, China. Measures of solitary behavior, autonomous motivation for solitude, attitude toward being alone, and time spent alone were collected using adolescents' self-report assessments. UCLA Loneliness Scale, Beck Depression Inventory, and Basic Psychological Needs Scales were measured as indices of adjustment.Results: Latent profile analysis revealed four distinct groups: absence of aloneness group (21.13%), positive motivational solitude group (29.01%), negative motivational solitude group (38.03%), and activity-oriented solitude group (11.83%). Differences emerged among these four groups in terms of loneliness, depressive symptoms, and basic needs satisfaction, with adolescents in the negative motivational solitude group facing the most risk of psychological maladjustment.Findings revealed the possible heterogeneous nature of solitude among Chinese late adolescents, and provided a theoretical basis for further understanding of adolescents' solitary state.